Tissue distribution and seasonal accumulation of carotenoids in Yesso scallop (Mizuhopecten yessoensis) with orange adductor muscle. (15th January 2022) - Li, Xue; Li, Ning; Zhao, Liang; Shi, Jiaoxia; Wang, Shuyue; Ning, Xianhui; Li, Yueru; Hu, Xiaoli
Highlights: Carotenoids accumulation in scallop was tissue- and gender- biased. 'Haida golden scallop' contains more carotenoids than normal scallop in most tissues. The ratio of pectenolone to pectenoxanthin differs among scallop tissues. Carotenoids content in muscle of 'Haida golden scallop' peaks in spawning season. Abstract: Carotenoids are colored compounds with important physiological functions. The Haida golden scallop, which has an orange adductor muscle, is a carotenoid-enriched variety of scallop Mizuhopecten yessoensis, an important aquaculture shellfish. In this study, we investigated the tissue distribution of the carotenoids, pectenolone and pectenoxanthin, in both Haida golden scallop and normal Yesso scallop. Both carotenoids were detected in all the sampled tissues of the two scallops, except in the adductor muscle of normal scallop. There were significantly more carotenoids in Haida golden scallop than in normal scallop, in the tissues of the mantle, female gonad, kidney, and adductor muscle. Increased carotenoid concentrations were detected in Haida golden scallop adductor muscle during the spring spawning season, indicating the effects of reproduction on muscle carotenoids accumulation. This study was the first systematic investigation of carotenoid distribution in Yesso scallop tissues and will benefit future research on carotenoid accumulation and function in scallops.